Psycho-social support needs to vulnerable children in orphanage homes in Nigeria (2014)
The study focused on the psychosocial support needs to vulnerable children in selected orphanage homes in Lagos, Oyo and Osun states. The study examined the categories of vulnerable children, needs of vulnerable children; type of care given to vulnerable children and the source of resources used in their homes. Purposive sampling technique was employed in the study with a sample size of 120 respondents. One hundred and twenty questionnaires, divided into 2 sections were administered to the respondents in order to collect data, data were collected by the researcher with the aid of one research assistance, data collected were analysed using frequency counts and chi-square statistics was employed to test for hypothesis. The results of the study showed that there is significant relationship between the needs of vulnerable children and the support given to them. Conclusion drawn from the study is that vulnerable children in these orphanage homes are well taken care of nutritionally, and are averagely supported psycho-socially (emotionally, educationally, medically, socially) by different organizations, particularly, Non-Governmental Organizations and Faith-based Organizations.